2016
DOI: 10.18632/oncotarget.11255
|View full text |Cite
|
Sign up to set email alerts
|

Identification of tumorigenesis-related mRNAs associated with RNA-binding protein HuR in thyroid cancer cells

Abstract: RNA binding proteins (RBPs) play a central role in cell physiology and pathology. Among them, HuR is a nuclear RBP, which shuttles to the cytoplasm to allow its RNA targets processing. HuR over-expression and delocalization are often associated to cell transformation. Numerous cancers display increased HuR protein levels and its high cytoplasmic levels has been associated with a worse prognosis.In our study, we first evaluated HuR expression in normal and cancer thyroid tissues and then evaluated its function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 63 publications
2
25
0
Order By: Relevance
“…The Western Blot analysis displayed a significant HuR overexpression in both ATC cells (Fig. 1), confirming data obtained in vivo (8).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The Western Blot analysis displayed a significant HuR overexpression in both ATC cells (Fig. 1), confirming data obtained in vivo (8).…”
Section: Resultssupporting
confidence: 86%
“…Moreover, various mRNA of tumorigenesis factors, oncogenes and anti-apoptotic factors have been identified as HuR targets (5). In a previous study, we demonstrated that HuR is overexpressed also in thyroid cancer (8).…”
Section: Introductionmentioning
confidence: 88%
“…Binding of ELAVL1 probably alters RNA conformation enabling LET-7 binding and translational inhibition of c-MYC, which would also interfere with miR17-92 expression (30). The increase in ELAVL1/HuR levels has been previously observed in thyroid cancers, and also correlated with poor prognosis (31). Therefore, ELAVL1 might be an important regulatory factor of cancer pathogenesis, ultimately regulating miR17-92 expression.…”
Section: Discussionmentioning
confidence: 92%
“…HuR expression has been investigated in 8 different thyroid cell lines: Nthy-ori-3.1, derived from normal thyroid follicular epithelial cells; BCPAP; K1; TPC1, derived from papillary thyroid carcinoma (PTC); FTC133; WRO, derived from follicular thyroid carcinoma (FTC); FRO; and SW1736, derived from anaplastic thyroid cancer (ATC) [ 97 ]. A significant overexpression of HuR protein was detected in all PTCs and in SW1736 cells, according to immunoblot analysis, whereas HuR positivity was higher in BCPAP compared to Nthy-ori-3.1 cells as shown by immunocytochemistry [ 97 ].…”
Section: Hur In Other Head and Neck Carcinomasmentioning
confidence: 99%
“…HuR expression has been noted in the majority of tissues from benign and malignant thyroid lesions, that is, hyperplastic nodules, Hashimoto thyroiditis, follicular adenomas, FTCs, PTCs, and ATCs, with a moderate to high immunoreactivity in almost half of those [ 97 , 98 ]. Normal thyroid tissue was negative for HuR immunostaining or showed lower expression compared to tumour lesions [ 97 , 98 ]. Cytoplasmic HuR immunostaining appears to clearly distinguish not only between normal and tumour tissue but also malignant and benign neoplasia.…”
Section: Hur In Other Head and Neck Carcinomasmentioning
confidence: 99%